Geist and Ge-Stell: Beyond the Cyber-Nihilist Convergence of Intelligence - Bensusan, Hilan Nissior (Cosmos and History: The Journal of Natural and Social Philosophy, 2020)
<!--[if gte mso 9]> <![endif]--><!--[if gte mso 9]> Normal 0 false false false EN-AU X-NONE AR-SA <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]--> This article argues that nihilism engages thought in a project of converging norms that assumes a contemporary form in Negarestani's inhumanism. Nihilism is described as a cyber-cosmopolitical project that engages with the (metaphysical) effort to extract the ultimate intelligibility of what exists. Heidegger's remarks on Ge-Stell are explored to question whether thought could possibly engage in anything other than the endeavor to turn the world into an artifice. The inhumanist reading of Geist is shown to be committed to the convergence of norms which is at odds with the very practice of reasoning. A post-nihilist Marxist picture of thought is then sketched according to which thought is taken to be a diverging force of production. In this alternative picture, the development of thinking leads to social, cybernetic and cosmopolitical relations that gradually diverge while distancing themselves from the current engagement in the extraction of the intelligibility of things.